Life Online - Animations for media education - National audiovisual institute KAVI (National audiovisual institute, 2023)
The Life Online series, produced by the National Audiovisual Institute KAVI, includes animations aimed at different age groups of children and young people. Educational material has been created to support discussions around each animation. The material can be used within early childhood, preschool and primary education, but also to support media education at home and for example in libraries.
Keywords: media literacy; new literacies; new media phenomena